The immunosuppressive effect of Siglecs on tendon–bone healing after ACL reconstruction. Issue 1 (January 2015) - Hu, Jiang; Yao, Bin; Yang, Xiao; Ma, Fang
Abstract The quality of the bone–tendon healing is very important to the surgery outcome after anterior cruciate ligament reconstruction. The necrosis of autograft and local new blood vessels occur after the surgery. The fibroblasts and mesenchymal cells presenting in the tendon–bone interface as well as the infiltrated of neutrophils and macrophages improve the biomechanical properties of the healing. We hypothesize that immunosuppressive effect of Siglecs which present on the surface of neutrophils and macrophages play the important roles to regulate acute local inflammatory reaction, maintain the physiological environment and induce the differentiation of the pluripotent cells to form the accepted histologic structure healing of the tendon–bone interface. It might be helpful to understand the mechanism of tendon–bone healing.